Scientific - Information Apparatus And Scientific Research Activity Of Museums (Eurasian Journal of History, Geography and Economics, 2023)
In the article scientific reference apparatus and scientific research activities of museums about information is given In particular , the main directions of research activities of museums are determined, on the one hand, by their affiliation to a certain specialized science, and on the other hand, by the place of museums in the system of social institutions. History museums are included in studies of historical sciences. Museums conduct scientific research in the field of museology as well as research in specialized disciplines